Risk factors for development of low back and neck pain in hospital nursing personnel - Stričević, Jadranka (Obzornik zdravstvene nege, 2012)
Introduction: A literature review of the impact of the work environment on the development of back pain identifies nursing personnel as a high-risk professional occupational group. The development of musculoskeletal disorders in personnel exposed to manual patient handling activity (patient lifting, repositioning and transfer) has been recognised as a major risk. Less substantiated data are available, however, on specific physical and psychosocial demands of work as independent risk factors for low back and neckpa in respectively. Methods: A cross-sectional study was conducted by usinga structured questionnaire and convenience sampling. The sample set comprised hospital nursing personnel from Maribor University clinical centre (n=575). The data gathered were statistically analysed. Results: The research results show that the majority of nursing personnel suffer from frequent episodes of low back (79.0%) and neck pain (65.9%). Further analysis established no statistically significant difference among the measured socio-demographic features, work environment and physical activity conducing to the development of either low back or neck pain. Discussion and conclusion:A literature review on spine problems afflicting nursing personnel indicates that pain in the lumbar region is a more common musculoskeletal disorder than the neck pain. The same results were also obtained by the present study. None of the risk factors were established as a predominant predictor for first-time occurrence of low back injuries and the development of either low back or neck pain. The proposed measures to maintain a healthy back and prevent back pain include adequate physical activity, avoidance of sedentary life style habits (like prolonged watching of television) and maintenance of normal body mass index.
Keywords: bolečina; dejavniki tveganja; delovno okolje; fizična aktivnost; hrbtenica; mišično-skeletna obolenja; musculoskeletal disorders; negovalno osebje; nursing personnel; physical activity; work environment; zdravstvena nega